Stability of transverse dental arch dimension with passive self-ligating brackets: a 6-year follow-up study - Franz Josef Willeit; Francesca Cremonini; Paul Willeit; Fabio Ramina; Marta Cappelletti; Alfredo Giorgio Spedicato; Luca Lombardo (SpringerOpen, 2022)
Abstract Objective The stability of the transverse expansion in passive self-ligating bracket treatments is a debated topic in orthodontics. However, to date, only 3 reports are available in the literature, with the maximum follow-up of 3 years after the end of therapy. The present study aims to evaluate the stability of orthodontic treatment with self-ligating brackets in a 6-year follow-up period of time. Materials and methods A sample of 56 non-extractive cases (of whom 33 females, mean age 16.9, SD = 9.0 years) consecutively treated with Damon® system was retrospectively selected. All patients received fixed retainers from canine to canine in both arches at the end of treatment, and no removable retainers were provided. The mean values of the transverse intercusp, transverse centroid and transverse lingual distances were evaluated for all teeth from canines to second molars in both arches. Each measure was calculated at four timepoints: before treatment (T0), at the end of treatment (T1), one year after treatment (T2) and six years after treatment (T3). Transverse diameters were measured for all teeth, starting from the canines to the second molars, for a total of 1680 observations, and subsequently compared in order to evaluate intra-treatment and post-treatment modifications. Results There were increases in all transverse dental measurements during active treatment. A statistically significant (p < .05) reduction of the transverse diameter was found, for upper and lower premolars, from T1 to T3. Conclusion The 6-year follow-up analysis detected that the initial transverse expansion showed a statistically significant relapse in premolars. No relapse was detected at the level of canines, due to the presence of fixed retainers, and minimal at first molars.